2017
DOI: 10.1002/bdd.2061
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing pharmacokinetic drug interaction precipitants in natural products: application to OATP inhibitors in grapefruit juice

Abstract: Natural products, including botanical dietary supplements and exotic drinks, represent an ever-increasing share of the health care market. The parallel ever-increasing popularity of self-medicating with natural products increases the likelihood of co-consumption with conventional drugs, raising concerns for unwanted natural product-drug interactions. Assessing the drug interaction liability of natural products is challenging due to the complex and variable chemical composition inherent to these products, neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Organic anion-transporting polypeptides (OATPs) are solute carrier membrane transporters. They have a major role in the absorption, tissue distribution, and elimination of endogenous molecules (e.g., steroids, bile acids, and bilirubin), drugs (e.g., statins), food components (e.g., Q and naringin), and toxins (e.g., alpha-amanitin and ochratoxin A) [ 18 , 19 , 20 , 21 , 22 ]. OATP1B1, OATP1B3, and OATP2B1 appear in hepatocytes [ 23 ]; furthermore, OATP1A2 and OATP2B1 are involved in the uptake of their substrates into enterocytes and/or the central nervous system [ 19 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic anion-transporting polypeptides (OATPs) are solute carrier membrane transporters. They have a major role in the absorption, tissue distribution, and elimination of endogenous molecules (e.g., steroids, bile acids, and bilirubin), drugs (e.g., statins), food components (e.g., Q and naringin), and toxins (e.g., alpha-amanitin and ochratoxin A) [ 18 , 19 , 20 , 21 , 22 ]. OATP1B1, OATP1B3, and OATP2B1 appear in hepatocytes [ 23 ]; furthermore, OATP1A2 and OATP2B1 are involved in the uptake of their substrates into enterocytes and/or the central nervous system [ 19 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…OATP inhibitors can decrease (inhibition of intestinal OATP2B1) or increase (inhibition of hepatic OATP1B1/1B3) plasma concentrations of substrate drugs triggering drug-drug or food-drug interactions [17][18][19][20][21][22][23]. In contrast to the widely expressed OATP2B1, for which inhibition by citrus fruit/juice/flavonoids provoking interactions with drugs has already been demonstrated [19,23,24], the role of the liver-specific OATP1B1 and OATP1B3 in mediating citrus-drug interactions is less clear, and the effect of polymethoxyflavones and the 7-O-rutinoside-flavanones on these transporters is completely unknown. We therefore investigated in vitro whether the 7-O-rutinoside-flavanones and the polymethoxyflavones could inhibit human OATP1B1 and OATP1B3 and also tested OATP2B1 inhibition, which was so far untested for sinensetin, didymin, and narirutin.…”
Section: Introductionmentioning
confidence: 99%
“…). The themes issue concludes with two further applications of relatively more complex models that explore intestinal metabolism, transport and associated interactions by Johnson et al and Liu et al . The latter helps readers to appreciate why a closer collaboration between the DMPK and pharmaceutics groups is essential in understanding aspects related to gut wall handling of drugs and associated drug interactions.…”
mentioning
confidence: 99%
“…Accordingly, the mechanism of the food effect is not limited to dissolution, solubility and gastro‐ empting rate matters but also to inhibition and induction of transporters and enzymes. Johnson et al analyze the effect of food using grapefruit on OATP2B1, which was demonstrated previously to be an intestinal drug uptake transporter by Tamai and Nakanishi in 2013 .…”
mentioning
confidence: 99%
See 1 more Smart Citation